Ectopic expression of the GRAS-type transcriptional regulator NSP2 in Parasponia triggers contrasting effects on symbioses - Alhusayni, Sultan; Kersten, Nick; Huisman, Rik; Geurts, Rene; Klein, Joël (Frontiers in Plant Science, 2024)
Plants strictly control root endosymbioses with nutrient-scavenging arbuscular endomycorrhizal fungi or nodule inducing diazotrophic bacteria. The GRAS-type transcriptional regulator NODULATION SIGNALING PATHWAY 2 (NSP2) is a conserved hub in this process. The NSP2-regulated transcriptional network is instrumental in balancing nutrient homeostasis with symbiotic interactions. NSP2 activity is modulated post-transcriptionally by a specific microRNA. Overriding this control mechanism by ectopic expression of a miRNA-resistant NSP2 transgene enhances the symbiotic permissiveness to arbuscular endomycorrhizal fungi. Such engineered plants may possess enhanced capacities for nutrient uptake. However, the trade-off of this strategy on plant development or other symbiotic interactions, like nodulation, is yet to be fully understood. We used the nodulating Cannabaceae species Parasponia andersonii as an experimental system to study the effect of ectopic NSP2 expression. Parasponia and legumes (Fabaceae) diverged 100 million years ago, providing a unique comparative system to dissect the nodulation trait. Six independent transgenic Parasponia lines were generated that differed in the level of NSP2 expression in the root from 6 to 95-fold higher when compared to the empty vector control plants. Analysis of these plants revealed a positive correlation between mycorrhization and the NSP2 expression level, as well as with the expression of the symbiosis transcription factor CYCLOPS and the rate-limiting enzyme in the carotenoid biosynthetic pathway PHYTOENE SYNTHASE1 (PSY1). Yet ectopic expression of NSP2 affected plant architecture and root nodule organogenesis. This indicates a significant trade-off when leveraging NSP2 over-expression to enhance endomycorrhization.